Cartographie De L’évolution Démographique Et Atteinte De L’objectif Du Développement Durable Dans Le Secteur De L’eau Dans Le Hollidjé Au Sud- Est Du Bénin - Djinadou, Rachade O.A.; Bigou, Léon Baní Bio; Oladjide, Azaria; Vodounou, Armand (European Scientific Journal, ESJ, 2017)
At the end of the Millennium Development Goals in 2015, the issue of access to water has not been fully addressed in developing countries in the face of increasing population. In Benin, despite the efforts made in this sector, rural populations are still faced with difficulties in accessing drinking water. This study aims to contribute to a better cartographic knowledge of the demographic evolution and its implications on the access to drinking water in Hollidjé. The study was carried out in 33 Holli villages in the municipalities of Pobè and Adja-Ouèrè. The censuses of 1979-1992-2002 and 2013 and the base of the water points of the Directorate General of Water of 2015 were used. These data have been processed using SPSS software 23, DEMProj for demographic projection by 2030 and ArcGis 10.1 for data spatialization and mapping. The study shows that Hollidjé is growing at a rate of 6.6% a year, double the national increase (3.50%). With a density of more than 200hbts / km², this territory has a low drinking water supply rate (minus 40% in 2013). By 2030, the Hollidjè population will double. Thus, the equivalent drinking water requirement will be 500 water points. At this pace, the objectives of sustainable development related to drinking water and sanitation may not be achieved if sectoral policies are not implemented.